Pengembangan Keterampilan Pengelolaan Sampah Menjadi Kompos Guna Mewujudkan Kawasan Bersih dan Hijau di Desa Tanjungkulon Kabupaten Pekalongan - Deny Aditya Puspasari; Bagus Nuari Priambudi; Retno Susanti (Kreativasi : Journal of Community Empowerment, 2023)
The problem of abundant leaf litter and the potential for livestock whose weight is not yet optimal is the basis for implementing this activity. This activity aims to improve community skills in utilizing existing resources in the surrounding location. This activity was carried out using a participatory method. There are several stages carried out in this method. The initial stage involves gathering aspirations for problems to deepen the existing substance at the location. Then the community is equipped with new knowledge and direct practice in processing existing resources around their village location. The output achieved by this activity was high enthusiasm from the community to be involved in this activity. The continuation of the process will continue to be accompanied and evaluated periodically. In the end, community independence can be created in utilizing the resources available around their village.